(untitled) (Journal of Organizational Psychology, 2020)
As demographics and volunteering interests evolve in the United States, nonprofit organizations are refining their engagement and recruitment strategies. This pilot study is uses a mixed method approach to uncover intrinsic motivators for volunteerism, asking 1) what are the primary motivations for individuals to volunteer?; and 2) what can be learned from these motivation factors to help an organization more effectively and efficiently engage and recruit new volunteers? This study suggests three motivations for volunteerism: personal gain, commitment to cause, and education. Considering these motivation factors may help nonprofit organizations provide new ways of engaging and recruiting volunteers.